Pendekatan Diagnostik dalam Menilai Kesulitan Belajar pada Siswa Sekolah Menengah Pertama - Firanti Sukma Hardiyani Lubis; Az-Zahra Juro; Lutfia Azahra; Maya Khofifah Silalahi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to describe and reveal data about the diagnostic approach in assessing learning difficulties in junior high school students. This research uses a qualitative research approach with a library research approach obtained from books, literature, articles, journals, and sites on the internet that are related to the research conducted. The results showed that the diagnostic approach has proven effective in identifying and dealing with learning difficulties of junior high school students. The form of learning difficulties in junior high school students is related to changes in their cognitive and emotional development. the form of difficulty that is often found is difficulty in exact lessons (Mathematics and Science). The causes of students having difficulty learning science are interest, motivation, concentration, learning habits and intelligence. To find out learning difficulties, teachers can conduct learning diagnostics through: first, student identification. second, conduct a diagnosis test with the most consecutive instruments using observation guides, written tests, interview guides and questionnaires and can conduct diagnostic investigations of learning difficulties by observation, interviews (interviews), diagnosis tests (including giving instructions, conducting tests, assessing test results, following up by adding remedial programs). third, provide assistance with tutoring.